Microbiological drinking water quality in educational and health centers in Costa Rica 2022 - Mora-Alvarado, Darner (2024)
This report studies the evolution of the coverage of access to water for use and human consumption, sanitation and hygiene in Costa Rica in the context of Latin America. Is based on the results of the different reports of the Progress of Drinking Water, sanitation in homes of 2021, 2018 and hygiene coverage data by countries of 2020 and 2022. In addition to the studies carried out by the National Water Laboratory. The results indicate that Chile and Costa Rica are at the forefront of safely managed water. However, Costa Rica, although it has very good coverage in at least basic systems for excreta management, the coverage of safely managed sanitation is only 17%. With respect to hygiene or hand washing with soap and water, the data provided is from only 65% ​​of the 20 Latin American countries, but there are also inconsistencies that show that hand washing, in most nations It is with water of dubious quality. Therefore, this study propose to move from basic to advanced hygiene services, using uncontaminated or safely managed water for hand washing with potable drinking water and soap.